Evaluation of Anthropometric Parameters of Central Obesity among Professional Drivers: A Receiver Operating Characteristic Analysis - Asif, Muhammad; Aslam, Muhammad; Altaf, Saima; Majid, Abdul; Atif, Saima (Kesmas, 2020)
Different anthropometric parameters have been proposed for assessing central obesity. The diagnostic performance of these anthropometric parameters and their ability to correctly measure central obesity for the professional community, like drivers, is questionable and needs to be assessed. The study aimed to examine the diagnostic performance of anthropometric parameters as indicators of central obesity in drivers as measured by waist circumference (WC) and to determine the best cut-off values for these parameters that would identify obese drivers. Anthropometric measurements from a cross-sectional sample of 197 professional drivers were taken under standard protocol. Receiver operating characteristics (ROC) analysis was used to examine the diagnostic performance and to determine the optimal cut-off point of each anthropometric parameter to identify centrally obese drivers. It was found that WC had a significant positive correlation with all other obesity indicators. The ROC curve analysis indicated that all the parameters analyzed had a good performance, but the waist-to-height ratio (WHtR) had a more predictive value of the area under the curve (AUC). Optimal cut-offs to identify central obesity in drivers were 0.55, 2.06, 0.95, and 25.44 for WHtR, conicity index, waist-to-hip ratio, and body mass index, respectively. These cut-off points for different indicators can be used to detect central obesity for drivers.